2008
DOI: 10.1097/pas.0b013e318159a2cb
|View full text |Cite
|
Sign up to set email alerts
|

Stage IA Vulvar Squamous Cell Carcinoma

Abstract: Early invasive vulvar squamous cell carcinoma (SCC) with less than 1.0 mm of invasion (FIGO stage IA) has been shown to have a minimal risk of lymph node metastasis and is associated with an excellent prognosis. The prognostic significance of other histologic parameters other than depth of invasion, however, remains controversial. Seventy-eight consecutive cases of vulvar SCC having a depth of invasion of 5.0 mm or less were reviewed and the clinical outcome compared with the type of surgical excision, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This study together with several previous examinations has demonstrated that differentiation grade plays an important role in the aggressiveness of a tumor and has a considerable impact on survival [9, 10, 13, 14, 17, 27]. …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This study together with several previous examinations has demonstrated that differentiation grade plays an important role in the aggressiveness of a tumor and has a considerable impact on survival [9, 10, 13, 14, 17, 27]. …”
Section: Discussionsupporting
confidence: 56%
“…differentiation grade, size and number of lymph node metastasis, presence of extracapsular spread), and depth of invasion was previously assessed using diverse criteria. The importance of proper measurement of the depth of invasion in vSCC was recently indicated by Yoder et al [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Additional research has shown that the infiltrative pattern of invasion is associated with a higher likelihood of lymph node involvement and decreased overall survival; however, stromal responses to vSCC have been relatively understudied. 1215 …”
Section: Discussionmentioning
confidence: 99%
“…Although an infiltrative pattern of invasion in vSCC has been frequently cited as an adverse prognostic factor, 1115 the literature is particularly sparse in regards to the importance of stromal responses to vSCC. In a review of 51 cases of vSCC, Ambros and colleagues reported that a subset of vSCCs showed a prominent fibromyxoid stromal response, and that these tumors were more likely to be associated with women of older age, clitoral involvement, nodal metastasis and overall poorer survival rates compared to tumors without a prominent fibromyxoid stromal response.…”
Section: Introductionmentioning
confidence: 99%
“…A stage IA tumour has <1% risk of lymph node metastases, compared to tumours invading 1.1–5.0 mm having lymph node metastasis in up to 20%. 93 Lymphadenectomy is recommended for any tumour beyond stage IA in most institutions and hence accurate assessment of invasion is critically important for guiding patient care. Caution should be exercised when assessing invasion in hair-bearing skin, as one-third of cases can involve the skin appendages as deep as 2.7 mm.…”
Section: Diagnostic Challenges and Differential Diagnosismentioning
confidence: 99%